Modeling a cataract disorder in mice with prime editing - Jianxiang Lin; Xingchen Liu; Zongyang Lu; Shisheng Huang; Susu Wu; Wenxia Yu; Yao Liu; Xiaoguo Zheng; Xingxu Huang; Qiang Sun; Yunbo Qiao; Zhen Liu (Elsevier, 2021)
Prime editing enables efficient introduction of targeted transversions, insertions, and deletions in mammalian cells and several organisms. However, genetic disease models with base deletions by prime editing have not yet been reported in mice. Here, we successfully generate a mouse model with a cataract disorder through microinjection of prime editor 3 (PE3) plasmids to efficiently induce targeted single-base deletion. Notably, a generated mouse with a high G-deletion rate (38.2%) displays a nuclear cataract phenotype; the PE3-induced deletions in mutant mice achieve high rates of germline transmission to their progenies, with phenotypic inheritance of cataract. Our data propose that modeling a genetic disease with a single nucleotide deletion in mice can be achieved with prime genome editing in vivo.